AB0142 A regulatory ccr10+ cd8+ t cell population differentiates psoriatic arthritis from psoriasis limited to cutaneous involvement. (12th June 2018) - Leijten, E.F.; van Kempen, T.S.; Olde Nordkamp, M.A.; Mertens, J.S.; Angiolilli, C.; Boes, M.L.; Radstake, T.R.
Abstract : Background: Few studies have compared the immune cell phenotype or function from patients with psoriatic arthritis (PsA) to patients with psoriasis limited to cutaneous involvement (Pso). Head-to-head comparisons of the immune cells in PsA and Pso can provide essential insights into the link between epithelial/cutaneous disease and rheumatic disease. Objectives: Compare the immune cell phenotype and function from patients with PsA compared to Pso. Methods: PBMCs were collected from 23 healthy controls, 21 patients with psoriasis in whom psoriatic arthritis was excluded by a rheumatologist (Pso), 23 patients with psoriatic arthritis (PsA) and 16 patients with ankylosing spondylitis. The Pso and PsA cohorts were free from immunomodulatory therapy and matched for demographics and skin severity. Extracellular and intracellular immunophenotyping using a highly standardised flow-cytometric approach detected over 110 different myeloid and lymphoid cell populations. Lesional and non-lesional skin biopsies and synovial fluid samples were collected from a subset of patients. Results: The circulating immune cell composition showed a remarkable overlap in Pso and PsA, and only one specific cell population was different: CCR10 +CD8+T cells, being enriched in PsA PBMCs as compared to Pso PBMCs. Further phenotypic and functional evaluation characterised them as effector memory, CXCR3-CCR6-, co-expressing the skin homing markers CCR4 and CLA, but lacking the gut homing marker α4β7. Upon re-stimulation, CCR10 +CD8+T cells showed low IFNγ production, high IL-10 production and were enriched for FOXP3 high CD25+ phenotype. Their frequencies in PBMCs were unrelated to joint disease activity and were stable throughout joint disease fluctuations. Synovial fluid displayed low frequencies of CCR10 +CD8+T cells whereas skin contained the most abundant CCR10 +CD8+T cell frequencies. Lesional psoriasis skin displayed relatively fewer CCR10 +CD8+T cells compared to non-lesional skin. Conclusions: CCR10 +CD8+T cells have regulatory properties and differentiate Pso from PsA. Future studies are needed to uncover if aberrances in regulatory, cutaneous CD8 +T cells precede the transition to joint disease. Disclosure of Interest: None declared